Analisis Semiotika Penggambaran Perempuan Bercadar dalam Film Pendek “Menjadi Aku Tak Harus Kaku” - Muhamad Lutfi Habibi (Kalijaga Journal of Communication, 2021)
The background problem of this research is how the depiction of face-veiled woman is found in the short movie "Menjadi Aku Tak Harus Kaku" produced by Islam-inspired online media, Islamidotco. The unit of analysis in this research is verbal signs and visual signs in each sequence which are identified through the technical understanding of the cinematic elements of the film. This research method uses Charles Sanders Peirce’s semiotic analysis of the triadic relationship between sign and object and the interpretation. The findings show that the depiction of face-veiled woman can be categorized into three meanings, that is experiencing a transformation that leads to tolerance, establishing relationships with other humans and the natural environment, and having a strong commitment in living life choices. The meaning of these signs are the icon that represents similarity in appearance and the index that reacts to phenomena that are often closely associated with face-veiled women in Indonesia.